2010
DOI: 10.1111/j.1474-9726.2010.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/apyrimidinic endonuclease 1, p53, and thioredoxin are linked in control of aging inC. elegans

Abstract: SummaryDeletions in mitochondrial DNA (mtDNA) accumulate during aging. Expression of the Caenorhabditis elegans apurinic ⁄ apyrimidinic endonuclease 1 (APE1) ortholog exo-3, involved in DNA repair, is reduced by 45% (P < 0.05) during aging of C. elegans. Suppression of exo-3 by treatment with RNAi resulted in a threefold increase in mtDNA deletions (P < 0.05), twofold enhanced generation of reactive oxygen species (ROS) (P < 0.01), distortion of the structural integrity of the nervous system, reduction of head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…Glyoxalase-1 is the major enzyme detoxifying methylglyoxal (MG), a precursor in AGE formation [8,10]. Increased accumulation of AGEs in turn further reduces glyoxalase-1 activity, induces ROS formation in a vicious feed-forward loop and ultimately contributes to reduced neuronal function and lifespan [11][12][13][14][15]. It has been shown that overexpression of glyoxalase-1 prolongs lifespan, establishing a causal connection between lifespan and glyoxalase-1 activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Glyoxalase-1 is the major enzyme detoxifying methylglyoxal (MG), a precursor in AGE formation [8,10]. Increased accumulation of AGEs in turn further reduces glyoxalase-1 activity, induces ROS formation in a vicious feed-forward loop and ultimately contributes to reduced neuronal function and lifespan [11][12][13][14][15]. It has been shown that overexpression of glyoxalase-1 prolongs lifespan, establishing a causal connection between lifespan and glyoxalase-1 activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, it is possible that Trx1 may exert a protective role against DNA damage through inhibiting translation by regulating phosphorylation of 4E-BP1 to save energy, possibly through cell cycle arrest by affecting p21 stability and allowing more time for DNA repair, thus eventually reducing MMS-induced cell death and enhancing cell survival. Indeed, protection of Trx1 against MMS-induced DNA damage could have been involved in DNA repair as redox signalling has been shown to affect APE1/Ref1 function, an apurinic/apyrimidinic endonuclease in the DNA base excision repair pathway (38,39), and APE1/Ref1 was shown to regulate the p53/p21 system (37,40). In addition, it was reported that the heat-stable cytosolic factor that promotes glucocorticoid receptor binding to DNA after MMS treatment is neither thioredoxin nor ribonuclease (41), suggesting that Trx1-mediated protection against MMS-induced DNA damage might be specific through certain cellular factors.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that deletion of the exo-3 gene, but not the apn-1 gene, results in decreased lifespan in the absence of FUdR in a ung-1-dependent manner (Kato et al, 2015). EXO-3 and APN-1 are AP endonucleases (Shatilla et al, 2005;Schlotterer et al, 2010;Zakaria et al, 2010;Yang et al, 2012), and UNG-1 is a uracil DNA glycosylase in C. elegans (Nakamura et al, 2008). In this study, we measured the lifespan of the exo-3 mutant in the presence of FUdR, and found that FUdR extended the lifespan of the mutant.…”
Section: Introductionmentioning
confidence: 99%